A central limit theorem for sums of functions of residuals in a high-dimensional regression model with an application to variance homoscedasticity test - Bai, Zhidong (2020)
We establish a joint central limit theorem for sums of squares and the fourth powers of residuals in a high-dimensional regression model. We then apply this CLT to detect the existence of heteroscedasticity for linear regression models without assuming randomness of covariates when the sample size n tends to infinity and the number of covariates p may be fixed or tend to infinity.